Dispersão larval radial pós-alimentar em Lucilia cuprina (Diptera, Calliphoridae): profundidade, peso e distância de enterramento para pupação - Gomes, Leonardo [UNESP]; Von Zuben, Claudio José [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2004)
Blowflies utilize discrete and ephemeral sites for breeding and larval nutrition. After the exhaustion of food, the larvae begin dispersing to search for sites to pupate or for additional food source, process referred as postfeeding larval dispersal. Some aspects of this process were investigated in Lucilia cuprina (Wiedemann, 1830), utilizing a circular arena to permit the radial dispersion of larvae from the food source in the center. To determine the localization of each pupa, the arena was split into 72 equal sectors from the center. For each pupa, distance from the center of arena, weight and depth were determined. Statistical tests were performed to verify the relation among weight, depth and distance of burying for pupation. It was verified that the larvae that disperse farthest are those with lowest weights. The majority of individuals reached the depth of burying for pupation between 7 and 18 cm. The study of this process of dispersion can be utilized in the estimation of postmortem interval (PMI) for human corpses in medico-criminal investigations.
Postfeeding radial larval dispersion in Lucilia cuprina (Diptera, Calliphoridae): depth, weight and distance of burying for pupation
Keywords: Blowflies; Calliphoridae; Lucilia; forensic entomology; larval dispersal